2022
DOI: 10.1177/08862605221119520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Domestic Violence Housing First Model on Survivors’ Safety and Housing Stability: 12-Month Findings

Abstract: Intimate partner violence (IPV) is a widespread and devastating phenomenon resulting in a myriad of long-term consequences for survivors and their children. IPV victimization not only has negative health and economic consequences, it has also been linked to homelessness and housing instability. In response, the Domestic Violence Housing First (DVHF) model is being used in some domestic violence (DV) agencies to help survivors attain safe and stable housing. The model includes using individualized advocacy and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In this comparative effectiveness study, survivors who received the DVHF intervention experienced improved housing stability, safety, and mental health over 2 years compared with those who received SAU. Results corroborated findings from a pilot study of the DVHF model as well as analyses of the current study’s data across 6 and 12 months . It is promising that DVHF resulted in relatively rapid improvements for survivors (6 months after they sought services) and that these positive changes were maintained across 12, 18, and 24 months.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this comparative effectiveness study, survivors who received the DVHF intervention experienced improved housing stability, safety, and mental health over 2 years compared with those who received SAU. Results corroborated findings from a pilot study of the DVHF model as well as analyses of the current study’s data across 6 and 12 months . It is promising that DVHF resulted in relatively rapid improvements for survivors (6 months after they sought services) and that these positive changes were maintained across 12, 18, and 24 months.…”
Section: Discussionsupporting
confidence: 84%
“…Results corroborated findings from a pilot study of the DVHF model 30 as well as analyses of the current study’s data across 6 and 12 months. 27 , 31 It is promising that DVHF resulted in relatively rapid improvements for survivors (6 months after they sought services) and that these positive changes were maintained across 12, 18, and 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Women experiencing homelessness face a range of health and social issues that often are intertwined and mutually reinforcing. These include a high likelihood of domestic violence or trauma, leading to housing instability ( Sullivan et al, 2023 ), and increased risk of mental health problems such as symptoms of depression, anxiety, and post-traumatic stress ( Beijer et al, 2018 ). Women in homelessness may also struggle with substance use, both to manage the stresses of homelessness and the subsequent underlying mental health or trauma issues ( Arnos & Acevedo, 2023 ; Beijer et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in California and Washington, 93% of DV survivors who received DVHF funding reported that they had learned more ways to plan for their safety and 96% of survivors reported feeling more hopeful about the future. 12 Additionally, a recent analysis of 345 homeless or unstably housed DV survivors found that DVHF resulted in greater housing stability and decreased economic abuse by partners over 6 months compared to DV survivors who received typical services. 13 In studies of homeless populations with significant psychiatric and substance-use comorbidity, those who received HF had higher rates of permanent housing, were better able to maintain permanent, independent housing, and had lower rates of substance abuse compared to those who did not receive HF.…”
Section: Introductionmentioning
confidence: 99%
“…The final aspect of the study design involves the inclusion of “control” sites and participants. While previous work has studied the outcomes of participants who receive DVHF assistance 13 , 26 , 27 or the difference between participants and non-participants at DVHF sites, 28 these approaches may underestimate the effects of DVHF programing because of spillover effects. Since demand for DV services always outpaces available funds and programs, program staff must often make difficult decisions about how and to whom services are offered.…”
Section: Introductionmentioning
confidence: 99%